Check of the taxonomy of freshwater fishes of Iraq - Al-Faisal, Abbas Jasim (Iraqi Journal of Aquaculture, 2022)
Taxonomic studies on freshwater fishes of Iraq were reviewed. Considerable differences in number of species that have been recorded in Iraqi freshwater were noticed, the number ranged from 44 to 70 species. The difference might be due to recording of synonyms or incorrect records. The continuous record of new species on various periods may have contributed to such variation. Thirty eight species, mainly cyprinids, fell into the disagreement category. A final list of the species which have received majority agreement was proposed with a total of 53 species and 12 families.